Systematic Literature Review: Mathematical Communication Ability through Quantum Learning Model Based on Self Efficacy - Hanif Jauhar Noor; Arief Agoestanto (Universitas Sembilanbelas November Kolaka, 2023)
Mathematical communication skills are very important skills in learning mathematics. Mathematical communication skills are also linked to self-efficacy. The purpose of this study was to determine the improvement and relationship of students' mathematical communication skills using Quantum Learning and self-efficacy. The Systematic Literature Review approach was used with the PRISMA method in this study. The electronic literature search source used is Google Scholar through Publish or Perish 8 which collects 994 articles, using national and international articles published from 2018-2023, indexed by Sinta 1-4 and indexed by Scopus, categorized as proceedings and journal articles, has full access and is categorized as a field of mathematics education. The results showed that self-efficacy affects mathematical communication skills and Quantum learning models and there is a relationship between self-efficacy and mathematical communication skills with Quantum learning models